The Protection Of Civil Rights Against Minority In The Case Of Divorce - Marsudi Utoyo; Kumba Digdowiseiso (Faculty of Law, Universitas Pekalongan, 2023)
The child is a legal subject who needs to be protected if there is a divorce. The wife or other woman designated by the terms and conditions of the law has the primary responsibility for raising the child until they are old enough to care for themselves. Children's parents are still obligated to provide a suitable environment for them to live in and to safeguard them, including by covering their living expenses. In accordance with the child's best interests and the idea of safeguarding children's rights, parents are still required to provide for and educate their children. Even if the biological mother is allowed hadhonah privileges in the custody case since she is the child's primary caregiver, the judge.